2014
DOI: 10.1111/aor.12330
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Characterization of a Decellularized Dermis‐Polymer Complex for Use in Percutaneous Devices

Abstract: To develop a method for making percutaneous devices that have high biocompatibility and do not induce downgrowth of epidermal cells, we prepared a partial decellularized dermis (DD)/poly(methyl methacrylate) (PMMA) complex (PDPC) with a PMMA rod firmly stabilized inside. The porcine decellularized tissue was chosen because of its high biocompatibility and mechanical properties, and MMA was used because it would adhere firmly to a polymer such as a catheter. The MMA filled the cavities in the dermis and polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Moreover, the vascular networks preserved in the decellularized scaffold also provide channels for perfusion and implantation in vivo. Studies have demonstrated that decellularized matrix based tissue regeneration is feasible for many hollow and parenchyma organs, such as bladder, 8 skin, 9 blood vessels, 10 heart, 11 lung, 12 kidney, 13 as well as liver. 14 Nonetheless, potential clinical application of DLM-based HLT may be plagued by the selection of scaffold source, considering that human derived DLM is also insufficient, and the application of xenogeneic DLM is hindered by potential risks of zoonosis and immunological rejection.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the vascular networks preserved in the decellularized scaffold also provide channels for perfusion and implantation in vivo. Studies have demonstrated that decellularized matrix based tissue regeneration is feasible for many hollow and parenchyma organs, such as bladder, 8 skin, 9 blood vessels, 10 heart, 11 lung, 12 kidney, 13 as well as liver. 14 Nonetheless, potential clinical application of DLM-based HLT may be plagued by the selection of scaffold source, considering that human derived DLM is also insufficient, and the application of xenogeneic DLM is hindered by potential risks of zoonosis and immunological rejection.…”
Section: Introductionmentioning
confidence: 99%
“…Since we used a small amount of photoinitiator and we eliminated the monomer inside the complex, cell toxicity was unlikely to be a problem. Furthermore, in our previous work we reported no sign of inflammatory response [4,9]. Therefore, we believe that this complex is safe to use as a base material for tissue interface.…”
Section: Discussionmentioning
confidence: 65%
“…The decellularized dermis was prepared under high-pressure using the methods described in our previous studies [4,9,[20][21]. In short, in order to dismantle dermis cells, the specimens were sealed inside polyethylene bags containing PBS, and hydrostatically pressurized using a cold isotactic pressurization machine (Dr.…”
Section: Preparation Of the Decellularized Dermismentioning
confidence: 99%
See 1 more Smart Citation
“…Kwangwoo Nam et al. of the Tokyo Medical and Dental University, Tokyo, Japan, reported on the development for making percutaneous devices that have high biocompatibility and do not induce downgrowth of epidermal cells. They prepared a porcine partial decellularized dermis (DD)/poly(methyl methacrylate) (PMMA) complex (PDPC) with a PMMA rod firmly stabilized inside.…”
Section: Biomaterials and Biocompatibilitymentioning
confidence: 99%